Effects of a Structured Weight-Bearing Exercise Program on Bone Metabolism Among Breast Cancer Survivors: A Feasibility Trial - Peppone, Luke J. (2010)
PURPOSE: Treatments for breast cancer, specifically hormonal therapy, accelerate bone loss (BL) among breast cancer survivors, leading to osteoporosis and an increase in fracture risk. Tai Chi Chuan (TCC) is a moderate form of weight-bearing exercise, equivalent to walking, and it has been shown to improve aerobic capacity and strength among breast cancer survivors and might also be effective in slowing bone loss in breast cancer survivors. This pilot study compared the influence of TCC with that of standard support therapy (ST; exercise control) on BL biomarkers among breast cancer survivors. PATIENTS AND METHODS: Randomly assigned breast cancer survivors (N = 16; median age, 53 years; < 30 months after treatment) completed 12 weeks (3 times per week, 60 minutes per session) of TCC or ST. Serum levels of N-telopeptides of type I collagen (NTx), a marker of bone resorption, and bone-specific alkaline phosphatase (BSAP), a marker of bone formation, were determined according to enzyme-linked immunosorbent assay at baseline and after the intervention. RESULTS: Using analysis of covariance, survivors in the TCC group experienced a greater increase in levels of bone formation (BSAP [µg/L]: before, 8.3; after, 10.2; change, 1.9 µg/L and 22.4%), compared with survivors in ST (BSAP [µg/L]: before, 7.6; after, 8.1; change, 0.5 µg/L [6.3%]). Survivors in the TCC group also experienced a significant decrease in bone resorption (NTx [nanomoles bone collagen equivalent; nmBCE]: before, 17.6; after, 11.1; change, −6.5 nmBCE; −36.9%), whereas women in the ST group did not (NTx [nmBCE]: before, 20.8; after, 18.8; change, −2.0 nmBCE; −9.6%). CONCLUSION: This pilot study suggests that weight-bearing exercise exerts positive effects on BL, through increased bone formation and decreased bone resorption. Further examinations of the influence of TCC on bone health are warranted.